2006
DOI: 10.1177/0885328206056378
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Surface Treatments on Anodic Oxide Film Growth and Electrochemical Properties of Tantalum used for Biomedical Applications

Abstract: Self-expandable nitinol (nickel-titanium) alloys and 316L stainless steel are the most commonly used materials in the production of coronary stents. However, tantalum (Ta) has already been used to make stents for endovascular surgery and may constitute an alternative to other materials because of its better electrochemical performance, namely its higher corrosion resistance, as well as its radio-opacity. The characterization of wet polished, chemically polished, wet polished anodized, and chemically polished a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 27 publications
(27 reference statements)
1
11
0
Order By: Relevance
“…Since nickel elution produces severe allergic issues, many of the research works on NiTi alloys were focused on improving the biocompatibility and corrosion resistance by suitable surface modification techniques [7][8][9]. The corrosion behavior of the alloy has been analyzed in various simulated body fluids such as Tyrode's, Hanks' , phosphate buffered saline (PBS), and 0.9 wt.% NaCl solutions [10][11][12][13][14][15][16][17]. Results of these studies showed that the electrochemical behavior and the nickel release rate vary from one type of solution to the other although the chloride content in these physiological solutions remained almost the same.…”
Section: Introductionmentioning
confidence: 99%
“…Since nickel elution produces severe allergic issues, many of the research works on NiTi alloys were focused on improving the biocompatibility and corrosion resistance by suitable surface modification techniques [7][8][9]. The corrosion behavior of the alloy has been analyzed in various simulated body fluids such as Tyrode's, Hanks' , phosphate buffered saline (PBS), and 0.9 wt.% NaCl solutions [10][11][12][13][14][15][16][17]. Results of these studies showed that the electrochemical behavior and the nickel release rate vary from one type of solution to the other although the chloride content in these physiological solutions remained almost the same.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, researchers are actively designing novel materials which possess improved mechanical and/or biological properties compared with currently used titanium‐based alloys. Some successful examples include β‐titanium alloys1, 2 which have a Young's modulus closer to that of natural bone and tantalum which has been considered to possess improved biocompatibility properties as compared with titanium 3. In contrast to developing new implant chemistries (which can lengthen implantation regulatory pathways), an alternative approach to improve implant functionality is to modify existing titanium‐based implant properties (particularly, surface properties).…”
Section: Introductionmentioning
confidence: 99%
“…They also reported corrosion-induced material loss less than 0.001 mm/yr. Silva et al have also performed EIS and microstructural studies on tantalum in 0.15 M NaCl solutions considering its application in endovascular surgery [16,17].…”
Section: Accepted Manuscriptmentioning
confidence: 99%